Politicization and political contests in and around contemporary multinational corporations: An introduction. (June 2018) - Clegg, Stewart; Geppert, Mike; Hollinshead, Graham
This article looks at core arguments in international business, organization studies and surrounding academic fields that focus on the study of politicization and political contests in and around multinational corporations (MNCs). Two evident streams of debate are identified. Equally evident is that these streams hardly connect. One stream is mainly interested in studying politicization from the outside, whereas the other is mainly interested in politicization from within. As a way of connecting both streams, we introduce the circuits of power framework. Next, we introduce the contributions of our Special Issue, followed by concluding comments which distinguish five emergent themes. First, we show how the application of the circuits of power framework sheds new light on the study of political contests of MNCs. Second, we highlight that the role of nation states has not lost its significance as, for example, political corporate social responsibility (CSR) approaches would have us believe. Third, dominant ideologies play an important role in establishing and controlling circuits of power in and around MNCs. Fourth, it is vital to take labour issues into account in this field of study. Fifth, there is increasing evidence that asymmetric and hierarchical forms of organizing do not disappear in new MNC network forms.